Asynchronous finite‐time dynamic output feedback control for discrete‐time switched linear systems with admissible edge‐dependent average dwell time - Wang, Mengjiao; Wu, Baowei; Wang, Yue‐E; Liu, Lili; Yan, Rongrong (Asian journal of control, 2024)
This paper is concerned with the problem of asynchronous finite‐time dynamic output feedback (DOF) control for a class of discrete‐time switched linear systems under the admissible edge‐dependent average dwell time (AED‐ADT) switching scheme. The main goal of the paper is to design a DOF controller to ensure that the resulting closed‐loop system is finite‐time bounded with AED‐ADT switching and has a specific H∞$$ H_{∞ } $$ performance. Firstly, some new sufficient conditions for stability criterion and H∞$$ H_{∞ } $$ performance analysis are established based on the multiple Lyapunov functionals technique and the linear matrix inequalities method. Secondly, a type of DOF controllers that guarantee that the closed‐loop system has desired performance is designed. Finally, the effectiveness of the proposed approaches is elaborated with a numerical example.